Effect of unloading confining pressure rates on macroscopic and microscopic mechanisms in diorite based on PFC3D - An, Xuexu; Huang, Juan; Duan, Xiaoxiao; Yang, Dengke (Frontiers in Materials, 2025)
IntroductionDeep underground excavation induces significant unloading damage in diorite, yet micromechanical mechanisms under varying unloading rates remain poorly understood.MethodsHerein, we employed the discrete element method to investigate the microscopic and macroscopic response mechanisms of deep hard diorite samples during the loading and unloading process. We performed numerical analysis at three unloading-confining-pressure rates using PFC3D. The macroscopic mechanical characteristics, particle displacement, number of contact force chain failures, and propagation and evolution characteristics of the spatial distribution of tensile shear microcracks along the axial and radial directions of the samples during the loading and unloading process were studied.Results(1) Peak strength and strain increased with reduced unloading rates, while confining pressure exhibited instantaneous fluctuations during unloading, signaling progressive fracture evolution. (2) Radial particle displacement and contact force chain failures showed nonlinear concave growth from core to surface, intensifying post-peak—indicating severe near-surface damage. (3) Microcracks propagated inward from the unloading surface, with tensile cracks predominating over shear cracks. Tensile crack density increased as unloading rate decreased.DiscussionLower unloading rates facilitate prolonged stress redistribution, amplifying force chain failures and microcrack density. This confirms that unloading-induced damage initiates near boundaries and propagates inward, with tensile mechanisms governing failure.